Motor cortex stimulation for refractory demyelinating disease-associated trigeminal neuralgia - Marcelo D Mendonça; Alexandra Seromenho-Santos; André Caetano; Carla Reizinho (SAGE Publishing, 2019)
Patients with demyelinating diseases (DDs) such as multiple sclerosis have a 20-fold higher risk of developing trigeminal neuralgia (TN). DD-related TN is more frequently refractory to the usual medical and surgical treatment. We report the case of a 57-year-old man presenting to our neurology outpatient clinic with a 12-year history of medical and surgical refractory TN associated with demyelinating lesions on magnetic resonance imaging. After a new failure of pharmacological treatment with oxcarbazepine, pregabalin, baclofen, and duloxetine, motor cortex stimulation (MCS) was performed, and the patient remained mostly pain-free, without any pharmacological treatment during the 3.5 years of follow-up. MCS may be a useful approach for DD-related refractory TN, and further studies can clarify its role in TN management.